Fiscal policy within the IS-LM framework - Naghshpour, Shahdad (Business Expert Press, 2014)
Governments have become an integral part of economics in modern societies. The extent of government involvement is not limited to legislation, foreign policy, or law and order. Governments intervene in economic affairs by collecting taxes and spending what they collect. The amount of taxes and who pays them, as well as the amount of government expenditures and who receives them, has a significant impact on income distribution. However, the main focus of the study of fiscal policy is on the overall economic impact of government involvement in the economy, instead of its distributional effects. While we know that when a person is taxed his or her utility is reduced, and when someone receives a payment, either because of selling something to the government or in the form of transfer payment, that person's utility increases. However, economic theory is not able to determine what happens to social utility when one person is taxed and another person receives the government payment. By not addressing the utility effect of government intervention in the economy the need for finding an answer to what happens to collective utility vanishes and allows us to focus on what happens to aggregate economic measures when the government intervenes in economic activities.